Development of Technology for the Recovery of Residual Lithium from Its Processing Waste - Costa, Alexandre Sylvio Vieira da; Sousa, Alexssander Ferreira de; Aguilar, Nubia Aparecida de; Campos, Tales Ceniro; Franco, Elton Santos (Electronic Journal "Fórum Ambiental da Alta Paulista", 2025)
Objective - To develop a sustainable and efficient technology for the recovery of residual lithium from waste generated during its processing, contributing to the mitigation of environmental impacts and the optimization of the utilization of this critical resource.Methodology - The research involved laboratory experiments based on flotation, chemical reaction, and washing, using different reagents, including vinegar, acetone, hydrochloric acid, sodium carbonate, kerosene, 99.5% alcohol, liquid soap, eucalyptus oil, and surfactant-containing remover. The samples were analyzed by X-ray fluorescence spectrometry, mass spectrometry, and X-ray diffraction, and the data were subjected to statistical analyses, including variation coefficients and Pearson correlation.Originality/relevance - The study fills a gap in lithium recovery from industrial waste, considering the technical and environmental feasibility of different processes. The research contributes to the circular economy and the reduction of dependence on primary sources, a topic of growing interest in the global energy transition.Results - The results indicated that acid leaching presented the highest efficiency in lithium concentration, achieving a 105% increase in metal concentration. A positive correlation was observed between lithium and aluminum (r = 0.956) and a negative correlation with calcium (r = -0.987), providing guidelines for process optimization. The chemical reaction method demonstrated greater reproducibility (CV = 28.48%) compared to flotation (CV = 97.74%) and washing (CV = 79.90%).Theoretical/methodological contributions - The research establishes parameters for optimizing lithium recovery processes, providing insights for future investigations aimed at improving efficiency and industrial scalability of these techniques.Social and environmental contributions - Recovering lithium from waste reduces the need for primary extraction, minimizing environmental impacts, water consumption, and emissions associated with conventional mining. The findings can guide public policies and industrial strategies focused on the sustainable management of mineral resources.
Keywords: Residual lithium; Lithium recovery; Sustainability; Industrial waste; Chemical processes